2004
DOI: 10.1081/ceh-200031839
|View full text |Cite
|
Sign up to set email alerts
|

β2Adrenergic Receptor GeneArg16GlyPolymorphism is Associated with Therapeutic Efficacy of Benazepril on Essential Hypertension in Chinese

Abstract: Our family-based study provided the first evidence that ADRB2 R16G polymorphism may play an important role in DBP response to benazepril treatment, although the magnitude of the effect appears to be modified by other risk factors such as plasma lipid and glucose profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
3
1
Order By: Relevance
“…Gly16 instead of the Arg16 allele of B2AR has been proved to be a risk for hypertension in humans (7). The B2AR R16G polymorphism is important for diastolic blood pressure response to benazepril treatment (24). However, we did not find any association between B2AR and the diseases investigated in this study.…”
Section: Modification Of Such Risk Factors To Prevent Cvds Is Well Escontrasting
confidence: 80%
“…Gly16 instead of the Arg16 allele of B2AR has been proved to be a risk for hypertension in humans (7). The B2AR R16G polymorphism is important for diastolic blood pressure response to benazepril treatment (24). However, we did not find any association between B2AR and the diseases investigated in this study.…”
Section: Modification Of Such Risk Factors To Prevent Cvds Is Well Escontrasting
confidence: 80%
“…Variants of ADRB2 have been associated with asthma exacerbations and salmeterol response 59,60 . However, antihypertensive and cardiac investigations of beta-blockers and ACEIs have yielded mixed results of the ADRB2 variants, rs1042713 and rs1042714, in predicting BP and congestive heart failure responses 10,17,56,57,[61][62][63] . Rs4994, a polymorphism in ADRB3, has been evaluated in hypertensive studies.…”
Section: Candidate Pharmacodynamic Polymorphisms Of Adrenergic Responsementioning
confidence: 99%
“…Indeed, the present study showed that Arg/Arg was associated with an increased risk of IC and also influenced the response to tricyclic antidepressant therapy compared with Arg/Gly or Gly/Gly. It has also been reported that Arg16Gly polymorphism of ADRB2 is associated with a greater decrease of the diastolic blood pressure in response to benazepril treatment (8), while the Gly16 allele of the ADBR2 gene confers resistance to parasitic infections (13). Cellular immunity and humoral immunity usually maintain a balance, but infection sometimes induces allergy or autoimmune disease by upsetting this balance.…”
Section: Polymorphism Of the Adrb2 (Arg16gly) Genementioning
confidence: 99%